?TEMPERATURE PROFILES IN ARGON ARCS BY OPTICAL EMISSION SPECTROSCOPY - AKBAR, SALIM; ETEMADI, KASRA (Biological Sciences - PJSIR, 1995)
A fully-automated emission spectroscopic set-up has been employed to measure temperature profiles in free- burning argon arcs (I atm, 13 mm electrode gap) by absolute line intensity of argon I lines at 6965, 7147 and 7635 A, under the assumption of LTE. The following salient results were obtained: (a) the peak temperature, 4 mm below the cathode tip, varied from 10I00 to 11050 K when arc current was varied from 75 to 300 A; (b) at 100, 150,250 and 300 A, peak temperatures of 10865, 11113, 11293 and 11750 K were calculated, respectively, at increasing distances of I to 4 mm below the cathode; and (c) isotherms obtained from simultaneous/consecutive measurements of 6965, 7635 and 7147 A lines at 200 A, yielded peak temperatures of 11658, 11157 and 11368 K, respectively, thereby suggesting that the self-absorption of the 7635 A line has only a small effect on the extracted temperature profiles.